Biodegradable and healable strain gauge based on Ti3C2TX MXene-gelatin hydrogel composite for eco-friendly applications - Hyun-Gu Han; Dong-Geon Lee; Ji-Yeop Kim; Mi-Jin Jin; Seungyoung Park; Doo-Seung Um; Chang-Il Kim (Materials Research Express)
Here, we report a novel MXene–gelatin hydrogel composite (MGHC) strain gauge with healable and biodegradable properties, aimed at bio-comfortable and environmentally sustainable applications. The performance of the MGHC gauge was demonstrated through resistance modulation at different strain levels, cyclic endurance, stretching speed sensitivity, and hysteresis properties. The gauge factor was close to unity, approximately 1.0, indicating a linear relationship between strain and resistance change and ensuring reliable measurements. The sensor exhibited cyclic endurance over 300 cycles, resulting in approximately a 3% increase in resistance, and sensitivity to stretching speeds was observed. Moreover, diverse applications were explored, including weight detection, joint angle measurement, and torsion angle sensing. The healable ability was investigated under varied temperature conditions to identify optimal healing conditions. Furthermore, the biodegradability of the sensor was assessed by observing complete degradation in phosphate-buffered saline and diluted hydrogen peroxide mixed solution, evaluating eco-friendly by-products. Overall, this study highlights the potential of the MGHC strain sensor for sustainable and biocompatible applications.